Molecular and biochemical characterization of two P450 enzymes in the ecdysteroidogenic pathway of Drosophila melanogaster. - Warren, J.T.; Petryk, A.; Marques, G.; Jarcho, M.; Parvy, J.P.; Dauphin-Villemant, C.; O'Connor, M.B.; Gilbert, L.I. (Proceedings of the National Academy of Sciences of the United States of America, 2002)
Five different enzymatic activities, catalyzed by both microsomal and mitochondrial cytochrome P450 monooxygenases (CYPs), are strongly implicated in the biosynthesis of ecdysone (E) from cholesterol. However, none of these enzymes have been characterized completely. The present data show that the wild-type genes of two members of the Halloween family of embryonic lethals, disembodied (dib) and shadow (sad), code for mitochondrial cytochromes P450 that mediate the last two hydroxylation reactions in the ecdysteroidogenic pathway in Drosophila, namely the C22- and C2-hydroxylases. When sad (CYP315A1) is transfected into Drosophila S2 cells, the cells metabolize 2-deoxyecdysone (2dE) to E and the [3H]ketotriol (2,22-dideoxyecdysone) to 22-deoxyecdysone. In contrast, dib (CYP302A1) is responsible for the conversion of the [3H]ketotriol to [3H]2dE. When cells are transfected with both dib and sad, they metabolize the [3H]ketotriol to [3H]E in high yield. The expression of sad and dib is concentrated within the individual segments of the developing epidermis when there is a surge of ecdysteroid midway through embryogenesis. This result occurs before the ring gland has developed and suggests that the embryonic epidermis is a site of ecdysteroid biosynthesis. This pattern then diminishes, and, during late embryogenesis, expression of both genes is concentrated in the prothoracic gland cells of the developing ring gland. Expression of dib and sad continues to be localized in this endocrine compartment during larval development, being maximal in both the late second and third instar larvae, about the time of the premolt peaks in the ecdysteroid titer.